The Influence of Cegah Anemia Remaja (Care) Educational Video on Knowledge and Perceptions of Anemia Prevention in Female Adolescents - Nabila Khairunisa Azzahra; Grhasta Dian Perestroika; Niken Bayu Argaheni; Iffah Indri Kusmawati; Revi Gama Hatta Novika (Journal of Health Promotion and Behavior, 2025)
Background: In adolescents aged 15-20 years, anemia is a disease that is susceptible, especially in young women. Early prevention efforts use educational videos motion graphics It has not been widely studied as to how much influence it has on knowledge and perceptions regarding the prevention of anemia in adolescents. This study aims to determine the effect of the Prevent Adolescent Anemia (CARE) educational video on knowledge and perceptions of preventing anemia in adolescents. Subjects and Method: A quantitative study was conducted on 68 teenage girls who were susceptible to anemia. This research used a quasi-experimental design that was held in February 2024 at Abi-Ummi Boyolali Islamic Boarding School. The dependent variable were adolescent knowledge and perception. The independent variable was Cegah Anemia Remaja (CARE) educational video. The difference in values between the two groups was analyzed using the Wilcoxon matched-pairs signed-ranks test. The influence of the CARE educational video on adolescents' knowledge and perceptions of anemia was examined using multinomial logistic regression. Results: The prevalence of knowledge of preventing anemia in adolescents is 58.8% sufficient and the majority's perception of preventing anemia in adolescents is good, at 94.1%. The effect of CARE educational videos on knowledge is significant (OR= 5.40; p <0.001) and on perception is also significant (OR= 5.48; p= 0.013). Conclusion: Health education through the Cegah Anemia Remaja (CARE) Educational Video has an effect on increasing knowledge and perception of anemia prevention in female adolescents.